The Microbial Functional Communities of Mollisol and Saline–Sodic Paddy Soils at Rice Heading and Harvest Stages in Northeast China - Jianfeng Zhang; Yuxin Yan; Dongxue Jiang; Shaoqi Huangfu; Hongyuan Ma; Lei Tian; Lihua Huang (Agriculture)
Rice is a primary food source for nearly half of the global population. In Northeast China, paddy soils are mainly classified into two distinct types: fertile mollisol and nutrient-deficient saline–sodic soil. Soil microbial communities play a critical role in maintaining the stability of rice agroecosystems; however, comparative studies on microbial diversity and functional systems across these soil types remain limited. This study aimed to systematically investigate the bacterial diversity, community structure, and functional characteristics of mollisol and saline–sodic paddy soils during the rice heading and harvest stages and to elucidate the differences between them. High-throughput sequencing technology was used to delineate the differences in bacterial communities and their functional attributes between these soil types. The results indicated that distinct variations occur in the alpha diversity and community structures of bacterial populations in both soil types during the rice heading and harvest stages. Typically, the alpha diversity indices were higher in mollisol paddy soil than that in saline–sodic soil. Notably, Actinomycetota showed a significantly higher relative abundance in saline–sodic paddy soil at the harvest stage, whereas Bacteroidota were more abundant in saline–sodic soil at both stages examined. A functional gene analysis via KEGG pathways revealed that carbon fixation pathways were more prevalent in mollisol paddy soil during the rice heading stage. Conversely, genes related to nitrogen metabolism were more abundant under saline–sodic conditions, suggesting a greater need for nitrogen in nutrient absorption by rice in these soils. Overall, bacteria in mollisol paddy soil appear to play more pivotal roles than those in saline–sodic paddy soil. This study not only sheds light on the functional dynamics of bacterial communities but also holds practical implications for soil management strategies in these contrasting environments.